Exploring the Nexus between Company ESG Performance and Dividend Policy: An Aggregate, Disaggregate, and Industry-Wide Panel Analysis - Harnesh Makhija; P. S. Raghukumari; Dipasha Sharma (Australasian Accounting, Business and Finance Journal, 2025)
In this study, we explore the relationship between Environmental, Social, and Governance (ESG) and Dividend policy (DP) for Indian companies from an aggregate (ESG effect), disaggregate perspective (E, S, and G effect) with industry-wide analysis. A system generalised method of moments technique was applied under a dynamic panel data setup to five years of data from 2015 to 2020 with 1520 firm observations of 304 companies from the NSE-500 index. This provided reliable and robust results. We found an ESG-DP positive relationship in the aggregate effect. The company's governance performance has no significant effect on DP; however, environmental and social performance both positively impact DP. Industry-wide analysis results show that the capital goods and health care industries positively associate with ESG-DP, whereas financial services and FMCG industries show no association. ESG-DP positive relationship signals that investments in sustainability can create high value for shareholders and other stakeholders. Though the overall ESG-DP nexus is positive, governance performance with DP is insignificant, indicating that companies with good governance scores have already leveraged positivity and, hence, focus only on capital appreciation. Industry results indicate that capital goods and health services industries invest more in ESG and pay dividends to improve their perception. The performance of ESG factors alone should not affect investor decisions in the financial services and FMCG industries. This pioneering study on India after the 2014 mandatory reforms explores the relationship between ESG-DP in terms of aggregate, disaggregate effect with an industry-wide analysis and recommendations.
Keywords: Indian Financial Market; Post-Merger Integration; Econometric Analysis; Fixed Effect Panel Regression; Generalised Method of Moments (GMM); Financial Institutions; Market Valuation; Operational Synergies; Strategic Alignment